Efficiency of marine shrimp farming systems - FREIRE, MARCOS; de Araújo Sales Júnior, Roosevelt; Gabriela Alves Costa, Maria; Lopes Ferreira, Rosane (Pubvet, 2020)
One of the great problems of shrimp culture is the maximization of crops and with it the emergence of new diseases, in the face of this problem, the aquaculture professionals, are seeking new practices that help in the expansion of the sector and the survival of the animals. In shrimp farming, animals can be submitted to different production systems comprising the various stages, such as single-phase, biphase or multiphase. In the multiphase system, the shrimp are initially stored in high densities, in primary intensive nurseries (BIP) and later in secondary nurseries (BIS), a strategy that strengthens the post-larvae and juveniles for the grow out or final phase. The goal of this work was to compare the effectiveness of shrimp production by evaluating the benefits of the multiphase system in shrimp culture and to discuss its possible advantages, limitations, applications and viability for the small farmer, as well as to the data used in the study came from the shrimp production in the Brazilian Northeast, where the production values of the single-phase system of grow out (direct settlement); and the multiphase system (primary nursery, secondary nursery, grow out) were compared in relation to the final survival of the shrimp. The following treatments were evaluated: Treatment 1 - (T1): Direct settlement in the ponds. Treatment 2 - (T2): Settlement in BIP, transfer to BIS; Treatment 3 - (T3): Settlement in BIP, transfer to BIS, transfer to ponds. The results of survival were: T1: 98%, T2: 45%, T3: 32%. In view of the data, it is possible to identify that the technification of the systems requires more skilled professionals, since three-phase systems present high densities, as well as increases the manipulation of the animals during the initial phases, in addition, these systems present a high cost of production, which hinder the small producer's financial return.
Keywords: Shrimp culture; intensive system; sustainability